Inhibitory effects of Spirulina in zymosan-induced arthritis in mice. - Remirez, Diadelis (2002)
The anti-inflammatory effect of microalgae Spirulina was studied in zymosan-induced arthritis in mice. Four days after the intra-articular injection of zymosan (15 mg/ml), Spirulina (100 and 400 mg/kg perorally) was administered to animals for 8 days. The mice were than killed and beta-glucuronidase was measured in the synovial fluid. Each knee joint was totally removed for histopathological studies. Spirulina significantly reduced the levels of beta-glucuronidase that had been increased by zymosan. Histopathological and ultrastructural studies showed inhibition of the inflammatory reaction, whereas no destruction of cartilage, well-preserved chondrocytes, and normal rough endoplasmic reticulum and mitochondria were seen. The anti-arthritic effect exerted by Spirulina as shown in this model may be at least partly due to the previously reported antiinflammatory and antioxidative properties of its constituent, phycocyanin. To our knowledge, this is the first report on the anti-inflammatory effect of Spirulina in an experimental model of arthritis.